Characterization of thermal stability, microstructures and properties of Al2TiO5 - and Ti3SiC2- based ceramics - Oo, Zeya (Curtin University, 2013)
The focus of this thesis was to study the thermal stability of Al2TiO5- and Ti3SiC2-based ceramics, and the oxidation characteristics of Ti3SiC2 through in-situ x-ray and neutron diffraction. The decomposition behaviour of Al2TiO5 in controlled atmospheres was studied in the temperature range of 20–1400°C. Al2TiO5 decomposed at 1100°C but reformed at 1350°C. In vacuum or argon, Ti3SiC2 decomposed to TiCx and Ti5Si3Cx above 1200°C. In air, Ti3SiC2 oxidized to anatase at 600°C, and formed an outer layer of rutile at 750°C and an inner mixed layer of rutile and cristobalite at 1350°C. Tridymite formed during cooling from 1350°C to room temperature.